2009
DOI: 10.2353/ajpath.2009.080576
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Is a Mediator of the Response of Fibroblasts to Irradiation

Abstract: Radiation causes soft tissue complications that include fibrosis and deficient wound healing. ␤-Catenin , a key component in the canonical Wnt-signaling pathway , is activated in fibrotic processes and wound repair and , as such , could play a role in mediating cellular responses to irradiation. ␤-Catenin can form a transcriptionally active complex with members of the Tcf family. A reporter mouse model , in addition to human cell cultures , was used to demonstrate that ionizing radiation activates ␤-catenin-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 45 publications
(65 reference statements)
3
28
0
Order By: Relevance
“…The associations between the Wnt pathway and MSCs (Salazar et al 2009) were further examined in the present study. We found that irradiation of nHLFs enhanced Wnt signaling, consistent with earlier reports (Gurung et al 2009). Importantly, coculture of nHLFs with HUMSCs attenuated the effects of irradiation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The associations between the Wnt pathway and MSCs (Salazar et al 2009) were further examined in the present study. We found that irradiation of nHLFs enhanced Wnt signaling, consistent with earlier reports (Gurung et al 2009). Importantly, coculture of nHLFs with HUMSCs attenuated the effects of irradiation.…”
Section: Discussionsupporting
confidence: 93%
“…Salazar et al (2009) observed that the CM of MSCs contained Wnt proteins that were capable of stimulating lung fibroblast proliferation through activation of the canonical Wnt/β-catenin signaling pathway. Another group have reported that canonical Wnt signaling is activated in nHLFs following irradiation, and that β-catenin mediates the effects of ionizing radiation on fibroblasts, acting to decrease the severity of radiation-induced soft tissue complications (Gurung et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A stress strain curve was generated, and loads were normalized to the cross-sectional area of the wound. The ultimate tensile strength and the work to failure were calculated (34,35).…”
Section: Methodsmentioning
confidence: 99%